## Solving (x+4)(x+4)

This expression represents the square of a binomial, specifically (x+4) multiplied by itself. There are two ways to solve it:

### 1. Expanding using the FOIL method:

**FOIL** stands for **First, Outer, Inner, Last**, a mnemonic to remember the order of multiplication:

**First:**x * x = x²**Outer:**x * 4 = 4x**Inner:**4 * x = 4x**Last:**4 * 4 = 16

Adding all the terms together, we get:

**x² + 4x + 4x + 16**

Combining like terms:

**x² + 8x + 16**

### 2. Using the Square of a Binomial Formula:

The square of a binomial formula states: **(a + b)² = a² + 2ab + b²**

In our case, a = x and b = 4. Applying the formula:

**a² = x²****2ab = 2 * x * 4 = 8x****b² = 4² = 16**

Combining the terms:

**x² + 8x + 16**

Therefore, the solution to (x+4)(x+4) is **x² + 8x + 16**.